Be star disc characteristics near the central object - Zorec, Juan (2007)
Context. A recent analysis of visual Fell emission lines of 17 classic Be stars using the self-absorption curve (SAC) method revealed that these lines are optically thick and that they form in circumstellar disc (CD) regions within two stellar radii from the central star on average. Aims. The aim of this paper is to study the physical characteristics of CD regions situated close to the central star. Methods. We used the Fell emission line optical depths derived for a sample of the above mentioned classic Be stars that are seen either nearly pole-on or equator-on. The disc properties sought are then inferred by reproducing the average pole-on and equator-on Fen line optical depths using simple CD models with different density and temperature distributions. Results. We found that the CD regions near the star, which account for the average Fe II line opacities obtained with the SAC method, have semi-height scales perpendicular to the equatorial plane h ≳ 0.5Ro and particle density distribution laws N(R) = No(Ro/R)n with n l∼ 1 at R ≲ 3Ro (Ro is the stellar radius; No is the particle density at R = Ro). Multi-scattering Monte Carlo simulations show that CD with particle density distributions N ∼ R-n, where n depends on the distance R and n ∼ 0.5 near the star, might account for the near-UV spectroplorarimetry of Be stars. CD with enhanced scale heights could explain the [Hα, E(J - L)] correlation as they may produce about the same Hα line emission, but larger IR flux excesses than thin discs. The enlarged CD scale heights do not contradict the existing interferometric measurements and should enable us to treat more consistently Balmer line emission formation in Be stars.